Comparison of avian and bovine spray-dried blood meal and whey levels in starter pig diets - Kats, L.J.; Dritz, Steven S.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 420 weanling pigs was used in a growth trial having two objectives. Objective 1 was to compare spray-dried avian blood meal and spray-dried bovine blood meal as protein sources in the phase II diet (d 7-21 postweaning). Objective 2 was to determine the appropriate level of dried whey for a phase II diet containing 2.5% spray-dried bovine blood meal. During phase I (d 0-7 postweaning), all pigs were fed a common high nutrient density pelletized diet containing 1.5% lysine, 20% dried edible grade whey, 7.5% spray-dried porcine plasma, and 1.75% spray-dried bovine blood meal. All phase II diets were formulated to 1.25% lysine, .9% Ca, and .8% P. In the comparison of avian and bovine spray-dried blood meals, the diets contained 2.5% blood meal and 10% whey. No significant differences occurred in average daily gain (ADG), average daily feed intake (ADFI), or feed to gain ratio (FIG) with use of avian and bovine spray-dried blood meal. The phase II diets comparing different whey levels contained 2.5% spray-dried bovine blood meal and whey levels of 5, 10, 15, or 20% substituted for corn and soybean meal on a protein basis. Linear and quadratic improvements occurred in performance with increasing whey levels for the 21 d growth period. However, linear and quadratic increases in the cost per pound of gain also occurred. In conclusion, avian and bovine blood meal appear to be comparable sources of protein for the phase II diet. Current economics indicate that approximately 10% whey is the optimal inclusion rate in phase II starter pig diets containing 2.5% spray-dried blood meal.
Keywords: Swine; Starter pigs; Whey; Spray-dried blood meal